Resposta :
Resposta:
g(x) = -5x + 2
g(-3) = -5(-3) + 2
g(-3) = 15+ 2
g(-3) =17
Explicação passo-a-passo:
Resposta:
OLÁ
[tex]g(x) = - 5 x+ 2 \\ para \: x = - 3 \\ substitui \\ g(x) = - 5x + 2 \\ g( - 3) = - 5 \times ( - 3) + 2 \\ g( - 3) = 15 + 2 \\ \blue{ \boxed{g( - 3) = 17}}[/tex]
espero ter ajudado
![Ver imagem ANDREYLUCAS15399](https://pt-static.z-dn.net/files/dc5/789c9897177645123d94951372d45181.jpg)
![Ver imagem ANDREYLUCAS15399](https://pt-static.z-dn.net/files/dde/25ad1f2a8b512ea73ad126bdcfad3346.jpg)